A study of place from the perspective of Heidegger's philosophical hermeneutics (Case study: Niavaran Cultural Center) - Faezeh Amiripouya; Khosrow Afzalian; Iraj Etesam; Mohsen Tabbasi (هنر اسلامی, 2022)
The present study explores the place in Niavaran Cultural Center from the perspective of philosophical hermeneutics. The final goal of the research is the location of Dasein according to the form, space and place in Niavaran Cultural Center. The question now is, from Heidegger's point of view, what are the components of architecture in architecture? How does Heidegger's philosophical hermeneutics manifest itself in the Niavaran Cultural Center?In order to answer the above questions, logical reasoning method was performed based on qualitative, descriptive and analytical research methods with a philosophical hermeneutic perspective. Data collection is in two categories: documentary (library) and field. The researcher can conduct in-depth interviews by discovering the dimensions of approximation by reading shared texts from Heidegger and Schultz narration of location and users, can be used as a model to provide patterns and components. Achieve quality effects on architectural spaces in the process of understanding place and feeling this identity with space. The components obtained from the research findings to understand the location of Niavaran Cultural Center include: orientation, identification, skyline, dialectics of outside and inside, geometry and environment, which can be read to the extent of the impact of these components in the process of creating space.